Identification of Human Proteins Interacting with the Protein IcsB of Shigella flexneri - Alzahrani, Ashwag (Université d'Ottawa / University of Ottawa, 2018)
Problem: Shigella is a gram-negative enteropathogen that, when passed through fecal particles from one host to the oral cavity of another host, causes an infectious disease known as shigellosis. One of the distinctive features of the infection by Shigella is its ability to bypass its host’s autophagic defenses. It does this through the use of a Type III secretion system, found in gram-negative pathogens like Shigella, which injects virulent proteins into the host cell. One of these proteins is IcsB; however, its exact function is not well understood. This study aims to better understand the role of this protein in the infection. Methods: A yeast two-hybrid screening test is used in this case to examine the interactions between variations of the protein IcsB, and a library of host proteins. Given IcsB’s high yeast toxicity and that resulted in the total absence of yeast colony formation, the first aim was to identify IcsB variants which expression would not prevent yeast growth. The second aim was to use the mutant with reduced cytotoxicity to perform a Y2H screen that will allow for the identification of candidate host proteins interacting with IcsB. Results: Two mutations of the IcsB protein grew in the Y2HG yeast strain, indicating a significant reduction in the protein’s toxicity. Of the cultures that reacted, high stringency and strong interaction was observed between four genes and IcsB proteins. Among the four identified clones that grew, three corresponded to the gene RNF2, while the last one corresponds to a non-coding sequence. Key control experiments revealed that the interaction of IcsB with RNF2 is likely false-positive. Thus, when screened full-length IcsB using new epithelial cells cDNAVI libraries, strong interaction was observed between three genes and our IcsB proteins. All the three genes DDX3X, FANCL, and SGT1 passed the false-positive interaction tests. It is interesting to notice that DDX3X and SGT1 interacted with catalytically active and inactive IcsB, suggesting that the interactions established between IcsB and prey proteins does not require the catalytic - C306A mutation and that IcsB most likely does not function as a protease against these two proteins. By contrast, FANCL bound catalytically inactive, but not catalytically active IcsB, suggesting it could be a substrate of IcsB. The literature provides some support for the putative role of DDX3X, FANCL, and SGT1 in regulating the vacuole escape of Shigella through IcsB action. Conclusion: The aim of this study was to determine the functional of IcsB in the vacuole escape of Shigella. This study successfully identified three candidates interacting partner proteins for IcsB. Key control experiments confirmed the interaction of IcsB with DDX3X, FANCL and SGT1. This study provides a basis for further research, with further study aimed at confirming these results during Shigella infection
Keywords: Shigella; Type III secretion system; IcsB; Protein-protein interactions; Yeast two-hybrid screening